Ethical Education in Scientific Relations Between Al-Kauniyyah and Ad-Diniyyah (Perspective Al-Kilani on Islamic Education) - Samsirin Samsirin; Dini Rofiatul Khoiriyah; Jenny Rismala Putri (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
Majid 'Irsan Al-Kilani's work explores the harmony of Islamic education in the connection between diniyyah and kauniyah understanding of Islamic educational politics. This research employs a descriptive qualitative approach and library research methodology, which consists of data collection or scientific works related to the object of research or collection, with library data to address problems whose primary focus is on the critical and in-depth study of the centeraka material concerned. The study's findings show that: (1) the problem of desire (iradah) and individual exploratory ability are the foundation of Islamic education; (2) the relationship that Al-Kailani established is based on the Kauniyah experience, the experience of al-ijtima', and the experience of religion; and (3) Al-Kailani's Islamic educational political thought is applicable to education in Indonesia in order to enhance and progress civilization.